ANALISIS EFEKTIVITAS MEDIA AUGMENTED REALITY DALAM PEMBELAJARAN IPA TERHADAP PENINGKATAN PEMAHAMAN KONSEP SISWA: A SYSTEMATIC LITERATURE REVIEW - Izzati, Naila; Taofik (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The low level of science concept understanding among elementary school students remains a significant educational challenge that affects learning outcomes and scientific thinking skills. The abstract nature of many science topics often makes it difficult for students to develop a deep understanding when learning relies primarily on conventional teaching methods. One promising solution is the use of Augmented Reality (AR), which can visualize abstract concepts in a more concrete and interactive manner. This study aimed to analyze the effectiveness of AR-based learning media in improving elementary school students’ understanding of science concepts through a Systematic Literature Review (SLR). The literature search was conducted using Google Scholar with relevant keywords. Articles were selected based on predetermined inclusion and exclusion criteria, resulting in 10 eligible studies published between 2022 until 2026. The data were analyzed using a qualitative descriptive approach by examining research characteristics, types of AR media, science learning topics, and their impact on students’ conceptual understanding. The findings indicate that all reviewed studies reported positive effects of AR implementation on students’ science concept understanding. Improvements ranged from moderate to high levels and consistently outperformed conventional learning approaches. The effectiveness of AR is attributed to its ability to visualize abstract concepts, enhance student engagement, and provide meaningful learning experiences. Therefore, AR has considerable potential as an innovative instructional medium for improving science concept understanding in elementary education.